2012
DOI: 10.1159/000345608
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Fumarate Hydratase Is Related to Tumorigenesis in Sporadic Renal Cell Cancer

Abstract: Objective: Although germline mutations of fumarate hydratase(FH) are a useful molecular marker of hereditary leiomyomatosis and renal cell cancer (RCC) syndrome, their clinical significance in sporadic RCC has not been studied in detail. The aim of the present study was to investigate possible correlations between the expression of FH and the clinical implications of sporadic RCC. Materials and Methods:FH mRNA levels were evaluated in 140 tumor specimens from patients with primary RCC and in 62 specimens of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…1C). Consistent with a broader role of FH in tumorigenesis, its transcriptional downregulation was found in sporadic clear cell carcinomas [30] and in colorectal cancer [31], and additional evidence suggests the involvement of FH mutations in breast, bladder, and testicular cancers [32]. These findings hint at a key role of FH loss in human cancers.…”
Section: Heterozygous Germline Mutations Of Fh Predispose To Hereditary Leiomyomatosis Andsupporting
confidence: 59%
“…1C). Consistent with a broader role of FH in tumorigenesis, its transcriptional downregulation was found in sporadic clear cell carcinomas [30] and in colorectal cancer [31], and additional evidence suggests the involvement of FH mutations in breast, bladder, and testicular cancers [32]. These findings hint at a key role of FH loss in human cancers.…”
Section: Heterozygous Germline Mutations Of Fh Predispose To Hereditary Leiomyomatosis Andsupporting
confidence: 59%
“…Patients with heterozygous germline mutations in the FH gene are susceptible to multiple cutaneous and uterine leiomyomatosis (MCUL), which is associated with an increased risk of developing papillary renal cell cancer and leiomyosarcoma ( Table 1 ) [ 35 , 36 , 37 ]. The sporadic loss of FH or transcriptional downregulation of FH was found in various cancers, such as pheochromocytomas, paragangliomas, neuroblastomas, adrenocortical carcinoma, ependymoma, osteosarcoma, bladder cancer, breast cancer, glioma, colorectal cancer, and testicular cancers [ 38 , 39 , 40 , 41 , 42 , 43 ]. Inactivation of FH compromises the TCA cycle and respiration, and tumor cells harboring mutations in FH were found to adapt to the glutamine-dependent reductive carboxylation reactions as an alternative pathway for the formation of αKG and citrate, which fuel the TCA cycle and generate NADH to feed into the electron transport chain for ATP generation and the maintenance of mitochondrial membrane potential [ 44 ].…”
Section: Mitochondrial Tca Cycle and Human Cancermentioning
confidence: 99%
“…FH germline mutations, which are often missense mutations and are particularly frequent in exons 4, 5, 7 and 8 (Bayley, Launonen, & Tomlinson, ; Picaud et al , ; Yoshinaga et al , ), have been found to decrease FH activity with the consequent accumulation of fumarate. Decreased functionality of FH predisposes individuals to several pathologies including multiple cutaneous leiomyomas, uterine leiomyomas, and the familial syndrome hereditary leiomyomatosis and renal cell cancer (HLRCC), which causes smooth muscle tumours and renal cell carcinomas (Bayley et al , ; Ha et al , ). HLRCC frequently involves a R190H mutation on the FH gene, which generates a dominant negative protein (Lorenzato et al , ).…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%